(untitled) (Research, Society and Development, 2022)
Introduction: The prolonged hospitalization process in the intensive care unit (ICU) is one of the determining factors for the increase in comorbidities in critically ill patients. In this context, the intensive care physical therapist is one of the professionals responsible for acting in a complex way in managing the functioning of the respiratory system with the optimization of ventilatory and motor function, in order to promote better health conditions for early discharge. Objective: to describe the sociodemographic and clinical profile of patients admitted to an intensive care unit (ICU), and to analyze the association of physical therapy with the length of stay in that unit. Methods: This is a cross-sectional and analytical study, with 18 patients of both sexes admitted to Intensive Care Units in the city of Jequié-BA. A questionnaire divided into two blocks was used: sociodemographic variables and clinical conditions. Relative and absolute frequencies were calculated, and the associative analysis was verified using the Fisher’s Exact Test. Results: There was a prevalence of female patients, aged 60 years or older, with elementary education and without a partner. The main cause of hospitalization was neurological diseases, followed by cardiovascular diseases. The length of stay and the amount of physical therapy treatment was less than or equal to nine. And there was an association between physical therapy visits and length of hospital stay. Conclusion: it is concluded that, among ICU patients, the majority are women, with advanced age, with low level of education and living without a spouse. In addition, in was observed that neurological diseases are responsible for the largest number of hospitalizations, and that these hospitalized patients had, for the most part, a hospital stay of less than or equal to nine days, as well as nine or less physical therapy visits. In addition, there was significant relationship between the amount of physical therapy attendance and the number of days hospitalized in the ICU.